2017
DOI: 10.37358/rc.17.2.5445
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Assessment of Interleukin 6 in Irreversible Pulp Inflamation

Abstract: The study aimed to assess the number, localization and distribution of interleukin 6 (IL-6) positive cells in healthy pulp, acute and chronic pulpitis. The study group included 48 patients aged between 18-72, treated in University of Medicine and Pharmacy Grigore T. Popa Iasi, Romania. The pulpectomy was performed on 42 patients diagnosed with acute and chronic pulpitis. The other 6 patients, without signs of dental caries or periodontal disease, were submitted to extractions of teeth for orthodontic purposes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…A 2012 meta-analysis showed that there is a statistical significant decrease in CRP and IL-6 levels after bariatric surgery. These cytokines are very important in the pathogenesis of some important diseases such as coronary heart disease and diabetes mellitus [6,11].…”
Section: Resultsmentioning
confidence: 99%
“…A 2012 meta-analysis showed that there is a statistical significant decrease in CRP and IL-6 levels after bariatric surgery. These cytokines are very important in the pathogenesis of some important diseases such as coronary heart disease and diabetes mellitus [6,11].…”
Section: Resultsmentioning
confidence: 99%
“…Both gram-negative and gram-positive bacteria in a caries lesion produce pathogens that activate the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) signalling pathway, resulting in the production of pro-inflammatory cytokines, such as IL-6 and IL-12 [15][16][17][18]. The expression of IL-6 is higher in acute pulpitis compared with chronic pulpitis and healthy human dental pulp tissue [19]. Streptococcus mutans is one of the major pathogens for dental caries and upregulates the expression of IFNγ, which induces IL-12 expression [20].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated human teeth with irreversible pulp alterations [10][11][12][13]26,[33][34][35] , or have been conducted in animals, and they have generally used dental erosion models [36][37][38][39] . The study models used have not faithfully reproduced cervical dentinal exposure in clinical patients 29,40) .…”
Section: Discussionmentioning
confidence: 99%